2017
DOI: 10.1155/2017/1945607
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Changes of Material Properties at Bone-Implant Interface during the Healing Process In Vivo: A Viscoelastic Investigation

Abstract: The aim of this study was to monitor the changes of viscoelastic properties at bone-implant interface via resonance frequency analysis (RFA) and the Periotest device during the healing process in an experimental rabbit model. Twenty-four dental implants were inserted into the femoral condyles of rabbits. The animals were sacrificed immediately after implant installation or on day 14, 28, or 56 after surgery. Viscoelastic properties at bone-implant interface were evaluated by measuring the implant stability quo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Many studies have reported that the bone–implant interface can influence peri-implant bone healing and the osseointegration process [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Not only does a rough implant surface ensure an improved bone anchorage when compared to a smooth implant surface, but it also promotes mesenchymal cell differentiation toward an osteoblastic phenotype [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that the bone–implant interface can influence peri-implant bone healing and the osseointegration process [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Not only does a rough implant surface ensure an improved bone anchorage when compared to a smooth implant surface, but it also promotes mesenchymal cell differentiation toward an osteoblastic phenotype [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osseointegration is defined as ''a direct structural and functional connection between ordered, living bone and the surface of a load carrying implant'' [3]. Successful osseointegration is considered to be a significant prerequisite for functional dental implants [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Osseointegration is defined as ''a direct structural and functional connection between ordered, living bone and the surface of a load carrying implant'' [3]. Successful osseointegration is considered to be a significant prerequisite for functional dental implants [3,4]. Implant stability is considered to be a reliable predictor for successful osseointegration in many studies and thus the measurement of stability can serve as a dependable method for the evaluation of osseointegration [3][4][5][6][7][8]23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, less invasive methods [9,10] have been proposed to assess the stability of microimplants. One of these methods [11,12] involves the Periotest M (Medzintechnik Gulden, Modautal, Germany), which has been used successfully. This study used the Periotest value (PTV) to determine the primary stability of the microimplants.…”
Section: Introductionmentioning
confidence: 99%